Islamic Value-Based Student Employability Scale: Validation with Rasch Model - Saputra, Rikas; Hambali, Im; Muslihati, Muslihati; Janu Setiyowati, Arbin; Lidyawati, Yenni; Ramadhani, Erfan; Che Nawi, Nur Raihan (Islamic Guidance and Counseling Journal, 2025)
In the era of globalization, universities in Indonesia are expected to produce graduates who are academically excellent and equipped with employability skills grounded in Islamic values. This dual expectation necessitates the development of assessment tools that align educational outcomes with religious and cultural contexts. However, existing employability scales often fail to capture the ethical and spiritual dimensions vital for Muslim students. This study aimed to develop and validate an Islamic value-based student employability scale that integrates core employability skills, Islamic work ethics, workplace spirituality, resilience, and motivation. Item development was based on a comprehensive literature review and expert consultation to ensure theoretical relevance and cultural appropriateness. The Rasch model was employed to provide accurate, bias-free measurement and to confirm unidimensionality. A cross-sectional design involving 1,192 students from 26 public Islamic universities in Indonesia was used, with data collected through an online questionnaire. Rasch analysis demonstrated strong validity and reliability (item reliability = 1.00; person reliability = 0.90), confirming the scale's ability to measure a single core construct. The Islamic value-based employability scale offers a psychometrically sound tool for assessing Muslim students' workplace readiness. It provides practical insights for Islamic higher education curriculum development and policy design.